Pesantren Kilat Ramadhan di Surau Ar-Rahman Sungai Beringin Kabupaten Indragiri Hilir - Sri Erdawati; Moh. Sain; Seri Yanti Siagian (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
This paper discusses the Ramadhan Islamic Boarding program conducted at Surau Ar-Rahman, Sungai Beringin Village, Tembilahan, Indragiri Hilir. It was necessary because it can provide education, training, and guidance to the younger generation, especially children and youth in reading short chapters of the Al-Quran with correct recitation, train and develop their memories so they can apply at least either obligatory or circumcision prayers. This program aimed at attracting participants' attention became constantly coming to the mosque, directing them to be positive, and performing beneficial activities during Ramadhan. This Ramadhan Islamic Boarding program was embraced enthusiastically and successfully because it affected participants' understanding of reading the Al-Quran. At the end of the program, they can read short chapters of Al-Quran with correct tajwid, including memorizing great short chapters of the Al-Quran.